Assessment of Cardiac Risk Index in Gynecological Oncology Surgical Patients - Hossain, Muhammad Mobarock; Ferdous, Jannatul; Ahmed, Chaudhury Meshkat; Khan, Moniruzzaman; Khan, Manir Hossain; Begum, Monowara; Masud, Mehidi; Faika, Jakanta (Cardiology and Cardiovascular Medicine, 2024)
Background: Surgical procedures in gynecological oncology patients carry significant cardiac risks due to the complex nature of the surgeries and the often-compromised health status of the patients. This study aims to assess the cardiac risk index in gynecological oncology patients undergoing surgery. Objectives: To assess the cardiac risk index using the Revised Cardiac Risk Index (RCRI) in gynecological oncology patients undergoing surgery. Methods: A prospective observational study was conducted at Uttara Crescent Hospital and Lab Aid Cancer hospital and super Specialty Center from August 2022 to December 2023. A total of 154 gynecological oncology patients scheduled for surgery were included in the study. The Revised Cardiac Risk Index (RCRI) was used to evaluate the cardiac risk before surgery. Data on patient demographics, medical history, RCRI scores, intraoperative findings, and postoperative cardiac complications were collected and analyzed. Statistical analyses of the results were be obtained by using window-based Microsoft Excel and Statistical Packages for Social Sciences (SPSS-24). Results: Of the 154 patients age mean ± SD were 49±12.3, while a little over half of the patients (54.55%) have had no prior abdominal surgery. Postoperative cardiac complications (2%), with the highest incidence among those in the high-risk group (40%). The most common complications were UTI (15%), VTE (Venous thromboembolism) (4.5%), Return to operating room (4%). The length of hospital stays and need for intensive care were significantly higher in patients with elevated RCRI scores. According to medical history hypertension (42.20%) and Chronic Obstructive Pulmonary Disease (COPD) is present in 11.68% of the population. A little over half of the patients (54.55%) have had no prior abdominal surgery. Uterine cancer is the most prevalent, affecting 54.55% of the patients. In cancer stage (FIGO) the majority of cancer cases (72.72%) are in stage I. Conclusion: The Revised Cardiac Risk Index (RCRI) is a valuable tool for predicting cardiac risk in gynecological oncology surgical patients. Patients with higher RCRI scores are at an increased risk of postoperative cardiac complications and may require more intensive perioperative monitoring and management. Early identification of high-risk patients allows for better preparation and potentially improved outcomes in this vulnerable population. Further research is recommended to refine risk assessment strategies and enhance patient care.